Seroprevalence of serum bactericidal antibodies against group W135 and Y meningococci in England in 2009 - Trotter, Caroline L; Findlow, Helen; Borrow, Ray (Clinical and vaccine immunology, 2012)
Serological surveillance has been used in the United Kingdom to inform vaccine policy for several infections, including those with group C meningococci. Meningococcal conjugate vaccines, containing capsular groups A, W135, and Y in addition to C, are now available, but their use in the United Kingdom is restricted to at-risk groups and travelers to areas of endemicity. The aim of this study was to establish a baseline for natural immunity for groups W135 and Y. Serum samples collected in 2009 from individuals of all ages were obtained from the Health Protection Agency Seroepidemiology Unit, which collects residual sera from participating laboratories across the country. Serum bactericidal antibody (SBA) activity against two reference strains, representing groups Y (strain M03 241125) and W135 (strain M01 240070), was determined with 1,191 sera using a standardized complement-mediated SBA assay, with complement derived from baby rabbits (rSBA). The age-specific geometric mean titers (GMTs) and percentages of individuals with rSBA titers of ≥ 8 were calculated, together with 95% confidence intervals (CI). Overall, 18.4% and 19.6% had rSBA titers of ≥ 8 for groups W135 and Y, respectively. Antibody prevalence varied by age. In general, rSBA titers were low for younger children, with serum samples from 7% and 13% of children under 5 years achieving titers of ≥ 8 against groups W135 and Y, respectively. GMTs peaked for 20- to 24-year-olds for group W135 (GMT, 7.1; 95% CI, 4.7, 10.9) and for 30- to 44-year-olds for group Y (GMT, 8.6; 95% CI, 5.9, 12.7). Unlike seroprevalence against group B meningococci, there was not an obvious peak in SBA titers in samples from teenagers. Natural immunity against group W135 and Y meningococci in England appears to be low.